On the Fabrication of Backside Illuminated Image Sensors: Bonding Oxide, Edge Trimming and CMP Rework Routes. (7th April 2015) - Cavaco, Celso; Peng, Lan; Sebaai, Farid; Verbinnen, Greet; Visker, Jakob; Olmen, Jan; Tezcan, Deniz Sabuncuoglu; Osman, Haris
Abstract : A comprehensive insight to a part of the fabrication process of backside illuminated (BSI) image sensor devices is here discussed. While showing the available process window, special emphasis is given to the key integration developments. The three main areas discussed in this work are bonding using different oxide layers, wafer edge trimming, and CMP rework routes. These processes are relatively new to imager fabrication and hence require mastering each step to achieve the yield requirements of an imager product.